Evaluating theory of change to improve the functioning of the network for improving quality of care for maternal, newborn and child health. - Albert Dube; Kondwani Mwandira; Kohenour Akter; Fatama Khatun; Seblewengel Lemma; Gloria Seruwagi; QCN Evaluation Group; Yusra Ribhi Shawar; Nehla Djellouli; Charles Mwakwenda; Mike English; Tim Colbourn (Public Library of Science (PLoS), 2024)
In 2017, WHO and global partners launched 'The Network for Improving Quality of Care for Maternal, Newborn and Child Health' (QCN) seeking to reduce in-facility maternal and newborn deaths and stillbirth by 50% in health facilities by 2022. We explored how the QCN theory of change guided what actually happened over 2018-2022 in order to understand what worked well, what did not, and to ultimately describe the consequences of QCN activities. We applied theory of change analysis criteria to investigate how well-defined, plausible, coherent and measurable the results were, how well-defined, coherent, justifiable, realistic, sustainable and measurable the assumptions were, and how independent and sufficient the causal links were. We found that the QCN theory of change was not used in the same way across implementing countries. While the theory stipulated Leadership, Action, Learning and Accountability as the principle to guide network activity implementation other principles and varying quality improvement methods have also been used; key conditions were missing at service integration and process levels in the global theory of change for the network. Conditions such as lack of physical resources were frequently reported to be preventing adequate care, or harm patient satisfaction. Key partners and implementers were not introduced to the network theory of change early enough for them to raise critical questions about their roles and the need for, and nature of, quality of care interventions. Whilst the theory of change was created at the outset of QCN it is not clear how much it guided actual activities or any monitoring and evaluation as things progressed. Enabling countries to develop their theory of change, perhaps guided by the global framework, could improve stakeholder engagement, allow local evaluation of assumptions and addressing of challenges, and better target QCN work toward achieving its goals.